Tilintarkastus ja evaluaatio Talouden ja sääntelyn vuoropuhelu - Ruohonen, Janne; Kihn, Lili-Anne; Oulasvirta, Lasse; Veikkola, Elisa (Tampere University Press, 2023)
This edited volume takes an in-depth look at current phenomena and issues in auditing, evaluation, and corporate governance. The external environment in which auditing operates - the economy, business, and the regulatory environment - is constantly changing. For example, the fight against climate change and other sustainability issues as a central mega-trend has put corporate responsibility at the heart of business. Addressing sustainability and other crises also highlights the need for responsible use and balance of public resources. The book contains 17 articles written by experts in the field. The book addresses current issues in a practice-oriented way, but with a strong scientific basis. The collection is multidisciplinary, as the issues addressed cross the boundaries between the private and public sectors, but also across disciplinary boundaries. It combines empirical, conceptual and legal research techniques. The book covers topics such as the verification of corporate accountability reporting, the quality of the audit, the auditor's responsibility to express an audit opinion and audit research. In addition, the book examines several topics in the field of evaluation and ownership steering, such as leadership in the context of the pandemic crisis and quality assessment in higher education. It also covers the monitoring of fiscal balance and corporate governance of municipal companies.